The Implementation of Contextual Teaching and Learning (CTL) in the Teaching of Integrated Skills - Yusmalinda Yusmalinda (LINGUA LITERA : journal of english linguistics and literature, 2017)
This article discusses about the implementation of contextual teaching learning (CTL) to solve three problems found in the teaching of integrated skills (Englishproficiency class): materials, methods (the integration of the four skills), and the students’ passiveness. Contextual teaching learning helps teachers relate materials or content to real world situations and motivate students to make connections between knowledge and its applications to their real lives or roles as family members, citizens, and workers and engage in the hard work that requires learning. This research was an action research done in three cycles and each cycle took five sessions with five phases: diagnosis, plan, action, and observation, evaluation and reflection. It was found that in the first cycle with five phases thethree problems found could be solved with the implementation of CTL, but there were still some students who were passive in the speaking activities in groupsbecause they had problems with their vocabulary, grammar, and self confidence. In addition, in the second cycle with five phases the problems found in the firstcycle could be handled, but there were still a few students that had the same problems found in the first cycle. Finally, in the third cycle with five phases againthe problems in the first cycle could be solved even though there was still one student who did not speak English actively.